Corporeality as a subject in contemporary philosophy - Struzik, Elżbieta (Folia Philosophica, 2010)
Report from the international conference “Corporeality as a subject of reflection in contemporary philosophy,” which took place from May 12 to 14, 2009, in Ustroń. The conference was organized by the Department of Philosophical Anthropology and Philosophy of Civilization and the Polish Philosophical Society, Katowice Branch.